Genotoxicity of Monosodium Glutamate: A Review on its Causes, Consequences and Prevention - Imam, Rabbani Syed (Indian Journal of Pharmaceutical Education and Research, 2019)
Monosodium Glutamate (MSG) is a common food additive used in processed foods to enhance the taste. The data available on Google scholar, NCBI, PUBMED, EMBASE, Wang fang databases, meta-analysis and Web of Science were reviewed to collect the information on the MSG-induced genetic damages, consequences and its mechanism. The retrieved information indicated that long-term consumption of MSG is associated with metabolic diseases, neurological and reproductive organ defects. Studies also suggested that MSG has the ability to induce genotoxicity. The damages on the genes have the tendency to implicate several diseased states in the host, not only in the present generation but also in the progeny. Considering the consequences of genetic damages on the population, this review was done to find the mutagenic potential of MSG, its causes and the preventive strategy for reducing the MSG-mediated genetic defects.
Keywords: Monosodium glutamate; Food additive; Genotoxicity; Oxidative stress; Antimutagens